The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.3109/10520295.2015.1024739
|View full text |Cite
|
Sign up to set email alerts
|

A stereological and histopathological study of the effects of exposure of male rat testes to mercury vapor

Abstract: Mercury is ubiquitous in the environment; it is an occupational pollutant and a potential toxicant. We investigated the effects of exposure of rat testes to mercury vapor (Hg(0)). Twelve male rats were divided into two groups of six: the rats of the Hg(0) group were exposed to mercury (1 mg/m(3)/day) in a chamber for six weeks; the control group rats were housed under the same conditions without exposure to Hg(0). After the experimental period, the testes were removed, sections of testis were evaluated histopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The present study reports that thimerosal exposure resulted in a decreased number of germ cell population at various stages within experimental groups. The outcomes of our study are in line with Altunkaynak et al, 2015 who reported a decrease in primary, secondary spermatocytes and the number of spermatids after Hg exposure, which is an integral part of thimerosal. Penna et al (2009) has suggested that mercury damage to spermatogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…The present study reports that thimerosal exposure resulted in a decreased number of germ cell population at various stages within experimental groups. The outcomes of our study are in line with Altunkaynak et al, 2015 who reported a decrease in primary, secondary spermatocytes and the number of spermatids after Hg exposure, which is an integral part of thimerosal. Penna et al (2009) has suggested that mercury damage to spermatogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…The mean volume of sinusoids and livers was calculated using both the Cavalieri and the point-counting methods (25,26). The systematic randomly sampling technique was performed to obtain the accurate and valuable results.…”
Section: Stereological Analysesmentioning
confidence: 99%
“…We divided the animals into control and experimental groups, each with six rats. The experimental group was exposed to 1 mg/m 3 /day mercury vapor by inhalation for 45 days within a special chamber as described in our earlier report (Altunkaynak et al 2015). The untreated controls were housed for 45 days in an identical chamber without exposure to Hg vapor.…”
Section: Experimental Animals and Proceduresmentioning
confidence: 99%